PERFORMANCE AND WORK MOTIVATION OF HONORARY TEACHERS IN ISOLATED VILLAGE (CASE STUDY IN MIS ULUPUS SA'ADAH HULU SUNGAI UTARA) - Hidayat Ma'ruf; Salafuddin Fitri (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This research aims to describe the performance and work motivation of honorary teachers at MIS Ulupus Sa'adah, a private Islamic primary education institution located in isolated villages. This research is qualitative with a case study approach. Data were collected through interviews, observation and documentation study. Data analysis was carried out through the stages of data reduction, data display, data verification, and conclusions. The results showed that although access to madrasah was quite difficult and the salary was not decent, the honorary teachers still showed good performance, this can be seen from; 1) discipline, 2) mastery of learning materials, 3) teaching ability, and 4) activities in teacher professional development. Their good performance is driven by the belief that teachers are a noble profession and providing useful knowledge is an investment in the afterlife whose rewards will always flow even though they have passed away. Their main goal of becoming teachers is not to get wages / salaries in the form of money, but the main thing is to get the value of merits from Allah SWT. They interpret teaching as a form of worship, not as a source of livelihood, so it must be carried out seriously and sincerely.